Relationship between Peer Interaction and Assertive Behavior of Student at SMPN 8 Maja - Syekha Aulia Mutia Zahra; Dwi Dasalinda (Universitas Muhammadiyah Enrekang, 2023)
This study aims to determine whether there is a relationship between peer interaction with the assertive behavior of students of SMPN 8 Maja in class VIII of the 2022/2023 academic year. The research method used is a correlational quantitative research method to be able to see the relationship between the x and y variables. The population used in this study was students of class VIII SMPN 8 Maja. The sample used consisted of 31 samples with saturated sampling technique. In testing the hypothesis using parametric data analysis with the Product Moment Correlation method, a Sig value of 0.003 is obtained. Decision making based on product moment correlation test criteria is if the Sig. < 0.05 then correlated. Based on the results of the product moment correlation test, it can be seen that the value of Sig. 0.003 <0.05 which means that peer interaction variables with assertive behavior variables are correlated. Meanwhile, the Pearson Correlation value was 0.521. With a significance level of 5%. So it can be seen that between peer interaction variables and assertive behavior variables have a moderate positive correlation. So it can be concluded that the higher the peer interaction that students have, the higher their assertive behavior. Vice versa, the lower the peer interaction, the lower the assertive behavior of students.